2020
DOI: 10.3389/fnhum.2020.00138
|View full text |Cite
|
Sign up to set email alerts
|

Visual Feedback Modulates Aftereffects and Electrophysiological Markers of Prism Adaptation

Abstract: Prism adaptation (PA) is both a model for visuomotor learning and a promising treatment for visuospatial neglect after stroke. The task involves reaching for targets while prism glasses horizontally displace the visual field. Adaptation is hypothesized to occur through two processes: strategic recalibration, a rapid self-correction of pointing errors; and spatial realignment, a more gradual adjustment of visuomotor reference frames that produce prism aftereffects (i.e., reaching errors upon glasses removal in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Effects around the P300 peak were characterized by increased P300 amplitude in response to visuomotor rotations in the placebo condition but not in the levodopa condition. This result replicates previous findings that visuomotor rotations increase the amplitude of P300 responses to feedback, and additionally suggests that this effect is dependent on dopaminergic signaling (Palidis, Cashaback, and Gribble 2019; Aziz et al 2020; MacLean et al 2015). However, disruption of P300 amplitude modulation by dopaminergic perturbation did not correspond to any behavioral changes, indicating that the modulation of P300 amplitude by sensory error is not essential for adaptation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Effects around the P300 peak were characterized by increased P300 amplitude in response to visuomotor rotations in the placebo condition but not in the levodopa condition. This result replicates previous findings that visuomotor rotations increase the amplitude of P300 responses to feedback, and additionally suggests that this effect is dependent on dopaminergic signaling (Palidis, Cashaback, and Gribble 2019; Aziz et al 2020; MacLean et al 2015). However, disruption of P300 amplitude modulation by dopaminergic perturbation did not correspond to any behavioral changes, indicating that the modulation of P300 amplitude by sensory error is not essential for adaptation.…”
Section: Discussionsupporting
confidence: 91%
“…This was expected, as trial-by-trial error correction induced by relatively small visuomotor rotations is thought to be driven primarily by sensory error-based learning mechanisms as opposed to dopaminergic reinforcement learning circuits (Diedrichsen et al, 2005;Ito, 2000;Krakauer et al, 2004;Tanaka et al, 2009;Jordan A. Taylor et al, 2010;Wong et al, 2019). It has previously been shown that visuomotor rotation increases the amplitude of the P300 ERP component, a centro-parietal ERP deflection peaking approximately 300-400ms following feedback presentation (Aziz et al, 2020;MacLean et al, 2015;Palidis et al, 2019). In the present study, we observed an interaction effect between feedback rotation and drug condition on the P300 amplitude.…”
Section: Discussionmentioning
confidence: 83%
“…The effect of realistic body representation does not seem to be due to the fact that the error feedback is more direct in the realistic representation. Aziz et al (2020) compared three types of feedback in three prism experiments: At the end of the pointing movement, either both the pointing finger and the target line were shown (direct error feedback, Experiment 1), or only the pointing finger without the target line (indirect error feedback, Experiment 2), or a representation of the pointing finger as a line and the target line (low-fidelity direct error feedback, Experiment 3). Although participants in Experiment 3 received direct error feedback, the aftereffect was significantly smaller than in the other two experiments, which did not differ significantly from each other.…”
Section: Vr As a Research Toolmentioning
confidence: 99%
“…It was first introduced by Hermann von Helmholtz in late 19th-century Germany as supportive evidence for his perceptual learning theory [64]. Studies have shown that humans quickly adapt to these sensory-motor transformations, to the point of having to adapt back to normal after the displacement ends [6,24,50,83]. Prism adaptation has been researched in detail with VR headsets instead of prism lenses [1,11,20,31,32].…”
Section: Direct and Indirect Inputmentioning
confidence: 99%
“…Among the first projects in smartphone-based head-mounted display (HMD) design started in 2011 in USC Institute for Creative Technologies by Olson et al [62]. They devised the FOV2GO device 6 , which was the first low-cost smartphone-based "cardboard" HMD prototype. Further evolution of the idea led to the creation of the first versions of modern VR headsets such as the Oculus Rift DK1 [12] and Google Cardboard 7 .…”
Section: Chapter 1: Introductionmentioning
confidence: 99%